2003
DOI: 10.1056/nejmoa021808
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak ofPseudomonas aeruginosaInfections Associated with Flexible Bronchoscopes

Abstract: This large outbreak of P. aeruginosa infections related to bronchoscopy was apparently caused by a loose biopsy-port cap in the bronchoscopes. Instrument safety and surveillance methods for bronchoscopy must be improved, and better recall procedures are needed for medical devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(43 citation statements)
references
References 14 publications
2
38
0
3
Order By: Relevance
“…These results were similar to what other studies had observed in the similar arrangement [15, 20]. In this study, higher contamination rates were observed in white coats used only during clinical duties when compared to those used both during clinical and non-clinical duties, suggesting a strong relationship between coat usage and patient care management.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results were similar to what other studies had observed in the similar arrangement [15, 20]. In this study, higher contamination rates were observed in white coats used only during clinical duties when compared to those used both during clinical and non-clinical duties, suggesting a strong relationship between coat usage and patient care management.…”
Section: Discussionsupporting
confidence: 92%
“…This study has also shown that staphylococcus aureus, contamination of white coats in medical, paediatrics and surgical ward was 3 % in all these units. However, Wong et al [13] and Srinivasan et al [20], reported that Staphylococcus aureus was less likely to be isolated from the white coats of health workers in a medical unit than those from a health worker in surgical or other units which was attributed to lower patient contact in the medical wards as compared to other units. However, based on the findings in this study, the low level of contamination in surgical wards could be attributed to the presence of infection prevention and control strategies at the time the study was undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…The capacity to control these outbreaks varies greatly and dependes on the reservoir. Outbreaks are usually circumscribed in time and attributable to a point source of infection which can be identified in the environment [4-8]. …”
Section: Introductionmentioning
confidence: 99%
“…P. aeruginosa biyofilmlerinin otomatik yıkayıcı ve dezenfektörlerden, hasarlı endoskop kanallarından uzaklaştırılması oldukça zordur. P. aeruginosa kolonizasyonu özellikle doku bütünlüğünü bozacak işlemlerde ve bağışıklığı baskılanmış hastalarda ciddi sorun oluşturur (10,13). Bronkoskop kaynaklı P. aeruginosa epidemileri olabilmektedir.…”
Section: İrdelemeunclassified
“…Bulaşma, kontamine aspirasyon valfleri, hasarlı biyopsi kanalları, kontamine topik anestezikler ve kontamine dezenfeksiyon makinelerinden kaynaklanmaktadır. Kontaminasyona bağlı olarak hem gerçek hem de yalancı salgınlar görülmektedir (7)(8)(9)(10).…”
Section: Introductionunclassified